Oncogenic microRNAs: miR-155, miR-19a, miR-181b, and miR-24 enable monitoring of early breast cancer in serum - Sochor, Marek; Basova, Petra; Pesta, Michal; Dusilkova, Nina; Bartos, Jiri; Burda, Pavel; Pospisil, Vit; Stopka, Tomas (BMC cancer, 2014)
BACKGROUND: MicroRNAs (miRs) represent a distinct class of posttranscriptional modulators of gene expression with remarkable stability in sera. Several miRs are oncogenic (oncomiRs) and are deregulated in the pathogenesis of breast cancer and function to inhibit tumor suppressors. Routine blood monitoring of these circulating tumor-derived products could be of significant benefit to the diagnosis and relapse detection of early-stage breast cancer (EBC) patients. METHODS: Aim of this project was to determine expression of miR-155, miR-19a, miR-181b, miR-24, relative to let-7a in sera of 63 patients with EBC and 21 healthy controls. Longitudinal multivariate data analysis was performed to stochastically model the serum levels of each of the oncomiRs during disease phases: from diagnosis, after surgery, and following chemo/radiotherapy. Moreover, this analysis was utilized to evaluate oncomiR levels in EBC patients subgrouped using current clinical prognostic factors including HER2, Ki-67, and grade III. RESULTS: EBC patients significantly over-express the oncomiRs at the time of diagnosis. Following surgical resection the serum levels of miR-155, miR-181b, and miR-24 significantly decreased (p = 1.89e-05, 5.41e-06, and 0.00638, respectively) whereas the miR-19a decreased significantly after the therapy (p = 0.00869). Furthermore, in case of high-risk patients serum levels of miR-155, miR-19a, miR-181b, and miR-24 are significantly more abundant in comparison to low-risk group (p = 0.026, 0.02567, 0.0250, and 0.00990) and show a decreasing trend upon therapy. CONCLUSIONS: OncomiRs are significantly more abundant in the sera of EBC patients compared to controls at diagnosis. Differences in oncomiR levels reflecting EBC risk were also observed. Testing the oncomiRs may be useful for diagnostic purpose and possibly also for relapse detection in follow-up studies of EBC.
Keywords: MicroRNAs; Neoplasm Grading; prognóza; mikro RNA; Adult; Aged; dospělí; Case-Control Studies; nádory prsu; senioři; lidé; ženské pohlaví; studie případů a kontrol; Biomarkers, Tumor; Breast Neoplasms; Humans; stupeň nádoru; Prognosis; Female; lidé středního věku; nádorové biomarkery; Middle Aged